Long-term effects of SGLT2 inhibitors on arrhythmias: a systematic review and meta-analysis - Li, Peipei; Chen, Weiwei; Chen, Rui; Zhang, Hanmo; Yu, Zhixi; Yan, Hongyu; Du, Beibei; Yang, Ping (Frontiers in Pharmacology, 2025)
AimsSodium-glucose co-transporter 2 (SGLT2) inhibitors are novel oral hypoglycemic agents strongly endorsed in the treatment guidelines for heart failure due to their cardioprotective benefits. However, their specific impact of SGLT2 inhibitors on arrhythmias incompletely understood. This systematic review and meta-analysis aimed to comprehensively evaluate the long-term effects of SGLT2 inhibitors on various arrhythmia types.MethodsWe systematically searched PubMed, Embase, Web of Science, and ClinicalTrials.gov from database inception to 30 June 2024, to identify randomized controlled clinical trials (RCTs) with a follow-up duration of at least 52 weeks. The primary outcome of the meta-analysis was atrial fibrillation (AF) or atrial flutter (AFL), and the secondary outcomes included ventricular tachycardia (VT), ventricular fibrillation (VF), and sinus bradycardia. The pooled risk ratios (RRs) with 95% confidence intervals (CIs) were used to estimate the incidence of arrhythmias.ResultsThirty-nine RCTs involving 107,770 participants were included. The results of meta-analysis revealed that patients treated with SGLT2 inhibitors had a reduced risk of AF/AFL compared with placebo (RR 0.86; 95%CI, 0.77–0.95; I2 = 0%; P = 0.003). There was no significant difference in the risk of AF/AFL between the high-dose SGLT2 inhibitors group and the low-dose SGLT2 inhibitors group (RR 0.78; 95%CI, 0.60–1.02; I2 = 0%; P = 0.07), although a decreasing trend in the high-dose group was noted. Similarly, no significant differences were found for VT (RR 0.99; 95%CI, 0.81–1.22; I2 = 0%; P = 0.96), VF (RR 1.06; 95%CI, 0.73–1.54; I2 = 0%; P = 0.75) or sinus bradycardia (RR 1.12; 95%CI, 0.57–2.18; I2 = 0%; P = 0.74) between the SGLT2 inhibitors and placebo groups.ConclusionSGLT2 inhibitors significantly reduce the risk of AF/AFL but have no notable impact on the risk of VT, VF, and sinus bradycardia. Additionally, different doses of SGLT2 inhibitors did not statistically influence AF/AFL incidence.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/home, identifier PROSPERO:CRD42022371089